2013
DOI: 10.21913/ijei.v9i1.845
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nigerian postgraduate students' experience of plagiarism: A phenomenographic case study

Abstract: In light of the high number of Nigerian students who gain admission to overseas universities for postgraduate studies, there is an increasing need to understand their background and previous study experiences. There are few studies of the experiences or views of Nigerian postgraduate students about the concept of plagiarism. The occurrence of plagiarism in the writings of some Nigerian students who travel overseas for graduate studies, like that of other students studying in a new academic context, has become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…The RPMPHE 2010 provides an explanation of plagiarism with lexical usage involving actions: "quoting other work" and "without accrediting", product: "partially or completely" and manner: "correctly and appropriately". The definition of plagiarism reflected in the literature as "copy and pasting", "absence of acknowledgement" and "presenting as their own" (Orim et al, 2013). However, the plagiarism definition offered by the RPMPHE 2010 appears to be lacking in detail and consistency.…”
Section: Intertextuality and Discourses Amongst Indonesian Plagiarismmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPMPHE 2010 provides an explanation of plagiarism with lexical usage involving actions: "quoting other work" and "without accrediting", product: "partially or completely" and manner: "correctly and appropriately". The definition of plagiarism reflected in the literature as "copy and pasting", "absence of acknowledgement" and "presenting as their own" (Orim et al, 2013). However, the plagiarism definition offered by the RPMPHE 2010 appears to be lacking in detail and consistency.…”
Section: Intertextuality and Discourses Amongst Indonesian Plagiarismmentioning
confidence: 99%
“…This lack of awareness of the importance of addressing plagiarism could have implications on perceiving plagiarism as a serious offence as plagiarism policy and practices in term of prevention may not be effectively be aligned. For example, academics may not communicate academic integrity and avoid plagiarism in their everyday teaching (Orim et al, 2013;Mahmud and Bretag 2013).…”
Section: Plagiarism Preventionmentioning
confidence: 99%
“…The danger with students overrating their academic writing is that they may not appreciate deficiencies in their academic writing abilities, and consequently, they may continue to commit plagiarism unintentionally. Poor understanding of plagiarism on the part of students put them at a higher risk of plagiarising (Leask 2006;Mahmood et al 2011;Orim et al 2013;Riasati and Rahimi 2013;Zafarghandi et al 2012).…”
Section: Brief Review Of Related Literaturementioning
confidence: 99%
“…The data from a study of Nigerian students (Orim et al 2013) suggested that students were more likely to get involved with academic dishonesty particularly when it is unrelated to examination cheating. This disposition was mostly due to their lack of awareness that a number of these acts constitute academic dishonesty (such as collusion, plagiarism, impersonation, etc.).…”
Section: Present Situation and Its Impact On Academic Integrity-related Issuesmentioning
confidence: 99%
“…Regarding dishonesty in written papers such as term papers (coursework), essays, and dissertations, little work has been done by researchers, possibly because this form of assessment is not greatly explored in most aspects of the Nigerian educational system due to large class sizes or high ratios of students to lecturer (100:1) as observed by Udotong (Obinna 2012). Some researchers (Adeniyi and Taiwo 2011;Aluede et al 2006) have barely mentioned them as existing forms of academic dishonesty in the Nigerian education system, while others have focused on plagiarism (Babalola 2012;Orim et al 2013). In their research, these authors have explored themes such as copying from sources (including the Internet) without citations, fabricating or falsifying a bibliography, falsifying quotations, listing real sources which were not read in a bibliography, using a submission for more than one subject without approval, copying from sources and presenting it as one's own, and submitting someone else's work as one's own.…”
Section: Development Of Research and Practice In The Field Of Academic Integrity In Nigeriamentioning
confidence: 99%